FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN PETANI SAWI MANIS DI KECAMATAN SUNGAILIAT KABUPATEN BANGKA - Lestari, Sevi; Purwasih, Rati; Yulia, Yulia (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
The agricultural sector which plays an important role in the Bangka Belitung Islands Province consists of the plantation and horticulture subsectors. Bangka Regency is one of the regions in the Bangka Belitung Islands Province which is currently planning regional development and economy in various sectors, one of which is the horticultural agricultural sector. The type of horticulture that is being developed in Bangka Regency is mustard greens. Farmers in Sungailiat District predominantly cultivate sweet mustard greens. Sungailiat District contributes the highest mustard greens production in Bangka Regency in 2022. However, currently sweet mustard greens farmers in Sungailiat District are faced with the problem of decreasing production quantities due to the increase in the quantity and price of inputs for production costs. Apart from that, the selling price is relatively low, so it can affect the income received. This research aims to analyze the factors that influence the income of sweet mustard farmers. The research method uses descriptive-quantitative analysis with income calculations and multiple linear regression. The research results showed that the average income of farmers from sweet mustard farming was IDR 3,997,339 per cultivated area per 1 planting season with a maximum income of IDR 16,112,050 per cultivated area per 1 planting season and a minimum income of IDR 443,583 per area cultivated per 1 planting season. The factors that significantly influence farmers income from sweet mustard greens farming in Sungailiat District, Bangka Regency, are the age of the farmer, family workers, the selling price of sweet mustard greens and the area of ​​sweet mustard greens farming, while farmer education has no effect on farmers income from sweet mustard greens farming